2018
DOI: 10.1016/j.geoderma.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of phosphorus availability in soil cultivated with ruzigrass

Abstract: Growing ruzigrass (Urochloa ruziziensis) in crop rotation systems has been suggested as a strategy to increase soil phosphorus (P) cycling and P availability. However, despite increased P lability shown in routine soil analysis, decreased grain yields of crops grown after ruzigrass have been observed. The objective of this study was to evaluate soil P availability to maize (Zea mays) in low or high-P soil cropped to ruzigrass. Soil P lability was evaluated using Hedley fractionation and pearl resin extractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 45 publications
(65 reference statements)
3
25
0
1
Order By: Relevance
“…In plants, P is an essential element required for development and reproduction, and it is one of the main components of the fertilizers necessary to sustain modern agriculture. In soils, the concentration of inorganic P (available to plants) ranges from 35 to 70% of the total P. This form of P shows low diffusion and high fixation rates in soils through ligand exchange by 1 : 1 clay minerals, Fe and Al oxides and hydroxides, and is thus precipitated as Fe, Al, and Ca phosphates [11,12]. Additionally, phosphate fertilizers are obtained from phosphoric rock, a nonrenewable resource, and whose reserves are running out [13].…”
Section: Introductionmentioning
confidence: 99%
“…In plants, P is an essential element required for development and reproduction, and it is one of the main components of the fertilizers necessary to sustain modern agriculture. In soils, the concentration of inorganic P (available to plants) ranges from 35 to 70% of the total P. This form of P shows low diffusion and high fixation rates in soils through ligand exchange by 1 : 1 clay minerals, Fe and Al oxides and hydroxides, and is thus precipitated as Fe, Al, and Ca phosphates [11,12]. Additionally, phosphate fertilizers are obtained from phosphoric rock, a nonrenewable resource, and whose reserves are running out [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to Almeida et al . (), ruzi grass should result in the accumulation of recalcitrant P o forms in soil. In the present study, it was observed that tropical grasses and microorganisms may expose recalcitrant P o forms, resulting in increased concentration of these P o forms, and showing that a great improvement in P availability may depend not only on the release of P from grass residues, but also on the mineralization of recalcitrant P o forms such as phytate.…”
Section: Resultsmentioning
confidence: 97%
“…Despite the fact that residual–P may be considered as a combination of inorganic and organic stable P forms strongly associated with the mineral fraction, P remobilization was mainly observed in residual–P due to grass cultivation. Several studies have shown that residual–P can be depleted by plant uptake (Almeida et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations